KEDUDUKAN AD/ART PARTAI POLITIK DALAM HIERARKI PERATURAN PERUNDANG-UNDANGAN TERKAIT KEWENANGAN UJI MATERIL OLEH MAHKAMAH AGUNG - Satriawan, Hera Alvina (Jurnal Hukum Bisnis Bonum Commune, 2022)
Association/Articles of Association is a written regulation made by a political party and contains matters as regulated in Article 2 Section (4) of Constitution no. 12 of 2011. The important role of political parties of Association/Articles of Association in regulating and directing the sustainability of a political party to ensure the implementation of a fair democracy has now changed. Political parties that have to act on behalf of the people but now only fight for the interests of the elites in political parties, so currently many conflicts occur solely to seek power. One of these conflicts is related to Association / Articles of Association which contradicts the Constitution and higher laws and regulations. Therefore, there is a legal vacuum regarding the institution authorized to examine the Association/Articles of Association of political parties. In this study, the author will examine the position of Association/Articles of Association of political parties in the hierarchy of legislation and whether the Supreme Court has the authority in testing AD/ART of political parties. The method of this study is normative law approach method by using statute approach and concept approach, then review and analyze using the law interpretation method. The result of the study is the Association/Articles of Association of political parties are not included in the hierarchy of laws and regulations as regulated in Article 7 of Law no. 12 year 2011. But the Association / Articles of Association of a political party can be categorized as a legal regulation based on Article 8 section (1) and section (2) of Law No. 12 of 011 and the implications of Association/Articles of Association’s classification as a piece of legislation then gives authority to the Supreme Court to examine the Association/Articles of Association of political parties.